One stage transanal versus one stage laparoscopic-assisted transanal endorectal pull-through in managing Hirschsprung’s disease in pediatric age group; a retrospective study - Ahmed Elrouby; Sameh Shehata; Saber Waheeb; Ahmed Khairi; Doaa AbdAl-Aziz; Baher Looka (BMC Surgery)
Abstract Background The management of Hirschsprung’s disease has evolved from the conventional route to the minimally invasive route in one stage either from the pure transanal route or with the assistance of laparoscopy. Our study compared the surgical and functional outcomes of both approaches. Methods Our retrospective study included 72 pediatric patients presented with Hirschsprung’s Disease to Elshatby University Hospital, 40 patients were treated by TAERPT (Group A) and 32 patients were treated by LAERPT (Group B). The two groups were compared as regards the personal data, the operative data, and the post-operative outcomes including the time of passage of stools, time of tolerating oral feeding, the duration of hospital stay, and the development of any early postoperative complications. Moreover, the frequency of defecation, constipation, enterocolitis, anastomotic stricture, and continence were assessed. Results The age at operation was significantly lower (p < 0.001*) in patients of Group A (13.95 ± 18.18) than in patients of Group B (32.03 ± 16.20). The total operative duration was not different between the two groups, however, a significantly shorter duration of the anal part (p < 0.001*) in Group B (47.81 ± 18) than in Group A (96.50 ± 38.60) was recorded. A significantly longer colonic segment (p < 0.001*) was resected in Group A (28 ± 4.05) than in Group B (22.70 ± 8.12). The hospital stay was significantly shorter in Group B (5.78 ± 2.41) than in Group A (7.20 ± 2.78). (p = 0.001*) The excised segment revealed a proximal aganglionic zone in four patients denoting a missed segment; three in Group B and only one patient in Group A. There were no differences as regards the early and late follow-up parameters. Conclusions Endorectal pull-through for the treatment of Hirschsprung’s disease could be approached either completely transanal or with the assistance of laparoscopy with nearly similar surgical and functional outcomes, however a longer operative duration with a shorter anal stage is recorded with the laparoscopic assistance. Furthermore, a shorter hospital stay could be achieved with the aid of laparoscopy. Trial registration Protocol ID: 0306356, Registration number: NCT06419998, 20/05/2024 - Retrospectively registered